Ionic Liquids as Catalyst for Synthesis of Some Aromatic Peracetylated N-(β-DGlucopyranosyl) Thiosemicarbazones - Dinh Thanh, Nguyen; The Hoai, Le; Thi Kim Giang, Nguyen; Van Quoc, Nguyen (Current Organic Synthesis, 2016)
Some acidic functionalized ionic liquids were evaluated for catalytic properties in synthetic reaction of peracetylated thiosemicarbazones having D-glucose moiety. For the first time, the ionic liquid, namely, 2-hydroxyethylammonium acetate proved to be an efficient, environment-friendly and easy catalyst for synthesis of these thiosemicarbazones in water as solvent under microwave irradiation, with high yields. The greener feature was found to be fairly general and the aqueous reaction media was reused in subsequent reactions with consistent activity. A series of N-(tetra-O-acetyl-β-D-glucopyranosyl)thiosemicarbazones of substituted acetophenones and benzaldehydes have been synthesized based on these investigated results.
Keywords: Acetophenones